Pengaruh Lokasi Dan Promosi Terhadap Kepuasan Konsumen Pada Archeries Cafe Di Tangerang Selatan - Putri Alifah Marta; Surti Wardani (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
Abstrak. The purpose of this study was to determine the effect of Location and Promotion on Consumer Satisfaction at Archeris Cafe. The research method used is quantitative descriptive associative causal, sampling technique using simple random sampling of the Slovin formula, obtained 99 respondents and a population of 10,569. Data analysis using validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, determination coefficient analysis, and hypothesis test. Data processing using SPSS version 26. The results of the study on the location variable obtained the regression equation Y = 15.433 + 0.349X1, the correlation coefficient value of 0.643 means that the two variables have a strong relationship level, the determination coefficient value of 0.610 (61%) while the remaining 39% is influenced by other factors or variables. Hypothesis test t count value 8.269> t table 1.984 with a significant level of 0.000 <0.05 so that there is a significant influence between location on consumer satisfaction at Acheries Cafe in South Tangerang. The results of the study on the promotion variable obtained a regression equation Y = 15.396 + 0.344 X2, a correlation coefficient value of 0.619 meaning that the variable has a strong level of relationship, a determination coefficient value of 0.559 (55.9) while the dependency (44.1) is influenced by other factors or variables. Hypothesis test calculated value 7.759> t table 1.984 with a significant 0.000 <0.05 so that there is a significant influence between promotion on consumer satisfaction at the archery cafe in South Tangerang. The results of the study obtained a regression equation of Y = 13.603 + 0.222X1 + 0.175X2. The coefficient of determination value is 0.668 (66.8) which indicates that consumer satisfaction is influenced by location and promotion variables, while the rest is influenced by other factors or variables. The results of the F-test are 40.489> F-table 3.09 with a significance level of 0.000 <0.05. Based on the results of the study above, location and promotion have a simultaneous and significant effect on consumer satisfaction at Archeries Cafe in South Tangerang Keywords: Location, Promotion, Consumer Satisfaction